Three-dimensional optical lithography for photonic microstructures - Scrimgeour, J; Sharp, D; Blanford, C; Roche, O; Denning, R; Turberfield, A (2006)
A rapid and flexible technique for optical fabrication by creating a device embedded in, and in registration with, a 3D photonic crystal using holographic lithography to define the underlying periodic microstructure was demonstrated. The new optical lithography techniques are intrinsically well adapted to 3D photonic-crystal device fabrication and uses a 3D interface pattern created at the intersection of four laser beams. It has been shown that by imaging the distribution of photo-chemical change induced by a holographic exposure,it is possible to align subsequent two-photon exposures to create device structures embedded in a 3D photonic-crystal lattice. This process has sufficient resolution to create embedded waveguide and microcavity structures by selectively modifying individual unit cells in the bulk of a 3D photonic crystals. The results show that holographic lithography can be combined with direct two-photon laser writing to photonic crystals with 3D structural modifications.